Evaluación de la obtención de hidrocarburos mediante pirólisis a partir de residuos de HDPE y LDPE (2018)
Through the next analysis, properties were determined such as moisture, amount of ash, volatile matter and fixed coal period, both of low density polyethylene as well as the high density, in order to obtain a quantitative result and establish the influence that these properties have on the yield product obtained from pyrolysis. To obtain hydrocarbons at the laboratory level, we started with a factorial design experiments in order to evaluate the yield product liquid and how it is affected by the type of polyethylene which is high and low density, and the temperature used were 600 °C and 650 °C. The characterization of the pyrolytic oil was determining its chemistry composition through of chromatography coupled to a mass detector, then was quantifying its density and viscosity. The solid product is characterizes through a total carbon analysis, determining at the same time the total organic and inorganic carbon. Finally the value in pesos is specified to obtain 1 kg of pyrolytic oil at the laboratory level. Keywords: HDPE, LDPE, pyrolysis, plastic, yield.